Determinan Kualitas Laporan Keuangan Desa Di Kecamatan Manisrenggo Dan Kecamatan Prambanan - Ananda, Afifah Intan; Fathah, Rigel Nurul (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
Abstact: Evaluating how village financial systems, budget preparation training, internal control system, and human resource competencien affect the quality of financial reports is the aim of this research. The urgency of this study stems from cases of budget irregularities at the village level, which have become a serious issue requiring attention, particularly in Manisrenggo Subdistrict and Prambanan Subdistrict. The research method employed is quantitative research using primary data. The population consists of 16 villages in the Manisrenggo Subdistrict and 16 villages in the Prambanan Subdistrict. The sample was determined through purposive sampling, resulting in 96 respondents as the sample. The analysis utilized SPSS 26. The research findings revealed a positive influence of the SISKEUDES variable, training in the preparation of the Village Budget (APBDes), and the Internal Control System (SPI) on the quality of financial reports. In contrast, human resource competence did not influence the quality of financial reports.